Chromatography Profiles of Terpenoid Compounds in The Extract of Sambiloto (Andrographis paniculata) Herb from Various Solvents - Mohammad Fajar Hadi Salim; I Made Arie Dharma Putra Nugraha; Farah Adilla; Luh Pratiwi Diva Yanti (Department of Chemistry Faculty of Science and Technology Walisongo, 2021)
Sambiloto (Andrographis paniculata) is widely used as a medicinal plant for Indonesians. The content of extracted bioactive compounds is affected by the polarity of the extraction solvent. This study aims to determine the effect of extraction solvent on the chromatographic profile of Sambiloto herb, especially terpenoid group using the TLC-Spectrophotodensitometry method. Sambiloto herb was extracted by sonication method using methanol, ethanol, ethyl acetate, and chloroform as the solvents. Chromatographic profiles were identified by stationary phase of TLC silica gel GF254 plate and a mobile phase of chloroform:methanol (10:1 v/v), observed visually, and scanned at 210 nm. The plate was sprayed with anisadehyd-sulfuric acid reagent and observed visually. The compounds that belong to terpenoid compounds, namely S2, S5, S8, S11, and S12, had a greater percentage of peak area than the total area so that they were categorized as major components. The extraction solvent for Sambiloto herb that provides the best chromatographic profiles was found in the solvent of methanol extraction.